Dėl lietuvių kalbos intarpinių veiksmažodžių - Kaukienė, Audronė; Pakalniškienė, Dalia (Baltistica, 1990)
ABOUT THE LITHUANIAN INFIX PRESENTSIn the modern Lithuanian and Latvian languages and their dialects the nasal infix verbs have the meaning of the state or its change. In the Indo-European languages the meaning of the verbs was a bit different. Some of the old languages — Greek, Latin, Sanskrit — etymological relationships mean an active action (Lat. f undo “lieju”, Skr. chinátti “pjauna”, Celt, bongid “laužo”), the others — the state or its change (Lat. ninquit “sninga”, Skr. dhvamsati “nyksta, yra”). The facts of the comparative languages give an idea that there might be nasal verbs in the Baltic languages with the meaning of active action.Eight out of 15 given verbs, having parallel present stems in a, ia and nasal infix, are used in the meaning of active action. The better part of them are effective (rañka, žañga, senka, reñta, šiñka, kruñša, pluñka, bruñka). This fact might be not new in the history of the Baltic languages. It might reflect the formation period of the verbs of the Baltic languages, when infix presents had no differentiated semantics.
Keywords: lietuvių; intarpiniai veiksmažodžiai; morfologija